Desert cheeses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Technology of making cheese from camel milk (Camelus dromedarius) FAO Animal Production and Health Papers, No 113, FAO 2001. 70 pp. ISBN 9251031541 US$ 12 Euro 13.40